2019
DOI: 10.1002/eji.201948098
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal expansion of TCRγδ+ and disappearance of IL4+ T cells suggest their involvement in the evolution from potential to overt celiac disease

Abstract: Celiac disease (CD) is characterized by a spectrum of intestinal inflammatory lesions.Most patients have villous atrophy (overt-CD), while others have a morphologically normal mucosa, despite the presence of CD-specific autoantibodies (potential-CD). As the mechanism responsible for villous atrophy is not completely elucidated, we investigated biomarkers specific for the different celiac lesions. Phenotype and cytokine production of intestinal mucosa cells were analyzed by flow cytometry in gut biopsies of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Moreover, in accordance with Vitale et al, pCD patients showed a high percentage of T cells co-producing IL-17, IL-4, and IFN-γ (Th0/Th17 p < 0.00005, Tc0/Tc17; Vitale et al, 2019). Notably, IL-17 is a pro-inflammatory cytokine, but a number of studies underlined its potential involvement in the prevention of gut mucosa inflammation (Mucida and Salek-Ardakani, 2009;Cukrowska et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, in accordance with Vitale et al, pCD patients showed a high percentage of T cells co-producing IL-17, IL-4, and IFN-γ (Th0/Th17 p < 0.00005, Tc0/Tc17; Vitale et al, 2019). Notably, IL-17 is a pro-inflammatory cytokine, but a number of studies underlined its potential involvement in the prevention of gut mucosa inflammation (Mucida and Salek-Ardakani, 2009;Cukrowska et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
“…In this follow-up study, in order to corroborate previous findings [17], we investigated these two lymphocyte populations in a larger number of pediatric subjects including patients with overt-CD, potential-CD and an age-matched control group of non-celiac subjects (henceforth identified as controls). In particular, we investigated the frequency of TCRγδ+ and IL4+ intestinal T lymphocytes by a multiparametric flow cytometry analysis on both intestinal cells freshly isolated from the mucosal samples and short-term T-cell lines (st-TCLs).…”
Section: Tcrγδ+ T Cells and Il4+ T Cells Are Inversely Correlated In Small Intestinal Mucosamentioning
confidence: 70%
“…Recently, we reported that the transition from a histologically normal intestinal mucosa of potential-celiacs to villous atrophy of overt-celiacs is associated with a marked intestinal expansion of TCRγδ+ T cells and a concomitant disappearance of IL4-producing T cells, likely CD4+ Th2 cells [17]. These preliminary findings strongly suggested that changes in the frequencies of these T cell populations in gut mucosa could influence the progression from mild towards severe mucosal inflammation and tissue damage.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations